2023
DOI: 10.1186/s12877-023-03757-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between long COVID, functional activity, and health-related quality of life in older adults

Abstract: Background Older adults experience persistent symptoms post-COVID-19, termed as Long COVID, affecting their physical and mental health. This study aimed to evaluate the effects of Long COVID, level of physical activity, and functional decline on older adults’ health-related quality of life post-COVID-19. Methods This cross-sectional study was conducted on 121 older adults with 60 to 90 years old post-coronavirus infection. The standardized metrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
0
10
0
2
Order By: Relevance
“…Some studies have shown that older adults have more severe long-COVID symptoms owing to the presence of underlying medical conditions and lower levels of physical activity. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that older adults have more severe long-COVID symptoms owing to the presence of underlying medical conditions and lower levels of physical activity. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…28 , 29 Long COVID is defined as persistent symptoms experienced in recovered patients from COVID-19 causing substantial disease burden. 30 In addition, patients with COVID-19 admitted to Intensive Care Units (ICUs) may have functional impairments; requiring treatment to fix the disability. Functional limitations must be assessed and multidisciplinary interventions must be designed in order to minimize disabilities and improve functional independence in patients recovering from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…As shown recently, irrespective of initial improvement, most individuals with a Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) infection will suffer from fatigue within three months following the onset of disease [5]. This non-specific group of symptoms is more often reported by patients with COVID-19 compared to other viral respiratory infections [6], and its presence significantly deteriorates the perceived quality of life and impairs both leisure activities and work performance [7][8][9][10]. It is also noteworthy that post-COVID symptoms, including fatigue, result in a significant burden of healthcare costs, as was recently revealed in a detailed analysis of nearly 30,000 people from the German Nationwide Inpatient Data [11].…”
Section: Introductionmentioning
confidence: 98%